1992
DOI: 10.1002/chin.199248064
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A New General Approach to Enantiomerically Pure Cyclic and Open‐Chain ( R)‐ and (S)‐α,α‐Disubstituted α‐Amino Acids.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In mammalian systems, molecular oxygen is directly incorporated in naphthalene metabolism [13], thus 1, 2, 3, 4-tetrahydronaphthalene nucleus may undergo biological oxidation to furnish a quinonoid structure which may also take a part in the reduction of living cell anaerobic glycolysis rate [14]. Recently, it has been reported that several tetrahydronaphthyl heterocycles posses potent anticancer activity against liver and breast cancer [15] and good precursors for the synthesis of various antidepressants [16], natural alkaloids (17), cyclic amino acids (18) and novel antagonists [19] of human TRPVI. Also, we cannot overlook the importance of chalcones and their cyclized analogues which were reported to have various chemotherapeutic activities.…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian systems, molecular oxygen is directly incorporated in naphthalene metabolism [13], thus 1, 2, 3, 4-tetrahydronaphthalene nucleus may undergo biological oxidation to furnish a quinonoid structure which may also take a part in the reduction of living cell anaerobic glycolysis rate [14]. Recently, it has been reported that several tetrahydronaphthyl heterocycles posses potent anticancer activity against liver and breast cancer [15] and good precursors for the synthesis of various antidepressants [16], natural alkaloids (17), cyclic amino acids (18) and novel antagonists [19] of human TRPVI. Also, we cannot overlook the importance of chalcones and their cyclized analogues which were reported to have various chemotherapeutic activities.…”
Section: Introductionmentioning
confidence: 99%
“…It was also used as a precursor to quinolines with dopaminergic activity, naphthols with anti-inflammatory activity and benzophenanthridine alkaloids with antitumor activity [124]. It has been used to synthesize natural alkaloids, cyclic amino acids and as novel antagonists of human TRPVI [125][126][127][128]. It was also used as a precursor to quinolines with dopaminergic activity, naphthols with antiinflammatory activity and benzophenanthridine alkaloids with antitumor activity.…”
Section: 7-dimethoxy-2-tetralone (C12h14o3)mentioning
confidence: 99%